Improving Students’ Speaking Skill Through Role Plays: A Classroom Action Research at MTs Mualimin Muhammadiyah Yogyakarta in Academic Year 2011/2012 - Syahruzah, Juang Kurniawan (ELTICS : Journal of English Language Teaching and English Linguistics, 2014)
The aim of this research is to find out how the implementation of role plays can improve the students’ speaking skill of grade VII of MTs Mualimin Muhammadiyah Yogyakarta in academic year 2011/2012 and how students respond to the use of role plays methods in teaching and learning process. This research is an action research. In this study the researcher uses action research theory proposed by Kemmis and McTaggart. The participants of the research are the students of grade VII of MTs Mualimin Muhammadiyah Yogyakarta in academic year 2011/2012. The research instrument used by the writer is in the form of observation checklist and test. The data in the research are mainly gathered through the use of pre-test, observation, questionnaires, and post-test. After the data are collected, the researcher analyzes them. The researcher uses the pre-test as the basis for measuring the students’ reading skill. The finding of the research shows that the implementation of translation and discussion can improve students’ speaking skill of grade VII of MTs Muhammmadiyah Yogyakarta in academic year 2011/2012. In the pre-test result, in which they formerly did not learn using discussion and translation, the mean of the pre-test was 55.64. After they learnt English using discussion and translation, the mean of the post-test was 63.3. The students’ response was positive when role plays methods were applied in teaching speaking. Keywords: Speaking, role play